Barriers and drivers to the adoption of energy-efficient technologies in the building sector: a survey in Brazil - Cristino, Talita Mariane (2020)
Energy is one of the most important factors for the growth of the world economy, thus the demand for it has increased over the years. Such a growing brings, among several issues, environmental impacts, mainly the increase of greenhouse gas emissions. For decades, the industrial sector was responsible for the greatest part of the energy demand, but as time went by the consumption shifted toward the building sector, which is responsible for 36% of the global final energy consumption and 40% of the total greenhouse gas emissions. Brazil, as well as worldwide, has been facing increasing energy consumption in the building sector. Such a scenario suggests urgency in reducing energy consumption. A way to reach this goal, without affecting the occupants’ welfare, is the adoption of building energy-efficient (BEE) technologies. There are several of these technologies available, bringing lots of benefits. However, there are barriers that hinder their adoption. Thus, before overcoming such barriers, it is necessary to know them. Therefore, the aim of this research is to identify the barriers that hinder the adoption of energy-saving technologies in the Brazilian building sector, and propose strategies to overcome them. To achieve such an objective, this research carried out a literature review over more than 450 articles gathered from the SCOPUS database, and 27 barriers were found to the adoption of energy-efficient technologies, which was classified into 6 groups, named as Financial/Economic; Market; Technological; Professional/Technical; Governmental/Political/Regulatory; and Cultural/Social/Behavioral. Such barriers were submitted to the judgment of Brazilian experts in order to capture their relevance to the national reality, by means of a structured questionnaire. A total of 1000 questionnaires were answered by professionals registered on the LinkedIn social network who had some academic education or professional experience related to building energy efficiency. Then, based on such questionnaires, a cluster analysis and factor analysis was performed in order to confirm the taxonomy proposed by the literature review, classifying at the same time, the categories according to their importance. The results confirmed the taxonomy proposed by the literature review, and the Governmental/Political/Regulatory and Financial/Economic barriers were the groups more important, according to the perception of the Brazilian experts. Furthermore, some strategies to overcome such barriers were proposed based on literature. Therefore, it is worth highlighting the main scientific contribution of this research is the theoretical consolidation on the barriers to the adoption of BEE technologies in the Brazilian building sector, in addition to presenting strategies to overcome them. It is worth noting that these contributions helped to fill scientific gaps related to the theme, which was presented in the research justification. As a practical contribution, the results of this research can be useful for the formulation of public policies, since it identified the barriers that most hinder the adoption of BEE technologies in Brazil. As these barriers are ranked in importance, it will be easy to start developing actions and programs focused on overcome the most important categories of barriers.